Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3384/lic.diva-105930
|View full text |Cite
|
Sign up to set email alerts
|

Patient Involvement : A Service Perspective

Abstract: For a long time, patients were seen as weak and passive recipients of care, whose only role was to provide information and comply with doctors' orders. This is beginning to change, and patients are more seen as autonomous, active, and involved collaborators in care, co-creating value with service providers and others. In parallel, the healthcare sector is changing due to an aging population, advances in technology, medical knowhow, and the prevalence of chronic diseases, which all call for a more involved pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 158 publications
0
2
0
Order By: Relevance
“…PPI is often framed as making the decisions and the policy process more legitimate by involving the public (input legitimacy), whereas involving the patient focuses on achieving legitimate results such as appropriate treatment and care, patient satisfaction, reduced costs and improved individual health outcomes (output legitimacy) (Snyder ). Nonetheless, citizens also have opinions on policy output, in particular on the effectiveness of achieving the goals citizens collectively care about (Scharpf ), for example universal coverage and access, disease prevention and value for money.…”
Section: Legitimacy and Representativenessmentioning
confidence: 99%
“…PPI is often framed as making the decisions and the policy process more legitimate by involving the public (input legitimacy), whereas involving the patient focuses on achieving legitimate results such as appropriate treatment and care, patient satisfaction, reduced costs and improved individual health outcomes (output legitimacy) (Snyder ). Nonetheless, citizens also have opinions on policy output, in particular on the effectiveness of achieving the goals citizens collectively care about (Scharpf ), for example universal coverage and access, disease prevention and value for money.…”
Section: Legitimacy and Representativenessmentioning
confidence: 99%
“…Although social and health‐care service clients are thus assigned an increasingly active role as experts with the right to participate in service development alongside professionals (Thompson, 2007), studies have indicated that their ability to contribute to actual decision‐making is surprisingly limited (e.g. Snyder, 2014). For instance, when clients in co‐development workshops analyzed by Weiste et al (2020a) were asked for their views on what client participation entailed, they highlighted the importance of actual decision‐making power, but viewed it as often lacking.…”
Section: Introductionmentioning
confidence: 99%